Woman with a Painful Rash - Leyan Shalabi; Wesley Eilbert (Clinical Practice and Cases in Emergency Medicine, 2025)
Case presentation: A 21-year-old woman with a history of eczema presented to the emergency department with a painful rash over the previous three days spreading from her left axilla to her left arm, left chest and left abdominal wall. The rash consisted of clusters of small, erythematous vesicles on hyperpigmented patches of skin. The patient was treated empirically with intravenous acyclovir for eczema herpeticum with improvement. Polymerase chain reaction testing of the fluid obtained from the rash vesicles later confirmed the presence of herpes simplex virus-1. Discussion: Eczema herpeticum is a cutaneous superinfection with herpes simplex virus on pre-existing sites of eczema. Left untreated, it can have a mortality rate over 50%. Early identification and treatment of this high morbidity condition with antiviral agents is key to improving outcome.